An empirical study on the economic effect of the Internet freedom - Junwon Lee; Chang-Young Jeon; Sung Wook Ji (International Telecommunications Society (ITS), 2018)
As information and communication technology developed, online sphere connected with Internet network appeared. That is, many elements of the existing offline sphere have moved to online without time and space restrictions. For example, various activities ranging from simple communication with others to business, schooling, consumption are carried out on the network. The media industry has also faced these changes. Newspapers, TV, and magazines, which had strong influence in the past, are already called traditional media. The advancement of the "Digital First" strategy such as online movements of newspapers emphasized by the New York Times and advancement of OTT services such as online movements of TV show that these traditional media are also moving to online networks. Many researchers have searched for factors affecting the use of the Internet or online markets in order to analyze these changes and various theoretical perspectives and issues have been suggested. While the development of the online media markets promotes economic growth and social development, and the optimistic outlook that positively influences individual thinking, behavior, and communication is spreading. On the other hand, in low-level countries, it may also indicate a tendency to be taken or subordinated to the global online media market competition...
Keywords: 330